New vanillin-derived diepoxy monomers for the synthesis of biobased thermosets. (June 2015) - Fache, Maxence; Auvergne, Rémi; Boutevin, Bernard; Caillol, Sylvain
Graphical abstract: Highlights: Synthesis of three vanillin-derived diepoxy monomers. Synthesis of renewable thermosets from these diepoxy monomers with isophorone diamine. Characterization of epoxy thermosets. Study of influence of monomer structure on Tg of epoxy networks. Comparison to bisphenol A-derived epoxy thermosets. Abstract: Biobased epoxy polymers were prepared from vanillin and compared to an industrial bisphenol A-based reference. This work directly continues the efforts engaged by our team to use vanillin as a biobased building block for polymer chemistry as it is an industrially available, non-toxic, renewable compound. Diglycidyl ethers were prepared from vanillin derivatives. These diepoxy monomers were formulated to give polymers that were compared to a bisphenol A-based material as reference of current use. In all cases, IPDA (IsoPhorone DiAmine) was used as it is a common industrial amine hardener. Thermal and mechanical properties of the biobased thermosets prepared were investigated. The influence of the monomer structure on these properties was discussed. The biobased polymers prepared were found to have tunable properties that could reach performances close to the current bisphenol A-based industrial reference. Vanillin-based epoxy polymers can thus be a sustainable alternative in many applications to the current non-renewable epoxy polymers based on bisphenol A.